The Effect of Task Implementation on the Speech of Tertiary-Level Chinese English Learners - Chen, Liping (Curtin University, 2024)
This thesis by compilation consists of five studies on implementing tasks to optimise L2 speech performance for tertiary-level Chinese English learners. The five studies expand Chinese English teachers’ knowledge of key instructional interventions related to the implementation phase of TBLT and the moderating effect of WM and L2 proficiency in these interventions. The studies provide a basis for teachers and researchers to develop L2 use through task performance and accommodate individual differences in TBLT